Transcriptome-wide association studies identify candidate genes for carcass and meat traits in meat rabbits - He, Hua; Tian, Xinyang; Kang, Zhe; Wang, Guozhi; Jia, Xianbo; Sun, Wenqiang; Lai, Song-Jia; Chen, Shi-Yi (Frontiers in Veterinary Science, 2024)
Meat rabbits are a small herbivorous livestock and have been popularly raised in China for producing high-quality meat. Therefore, it is economically important to genetically improve both carcass performance and meat quality in meat rabbits. However, we still know less about the underlying candidate genes that may determine phenotypic variation on carcass and meat traits of meat rabbits. The main objective of this study was to identify candidate genes whose mRNA expression levels may be significantly involved in regulating carcass and meat traits of meat rabbits based on the transcriptome-wide association studies (TWAS). Five carcass traits of the carcass weight (CW), dressing out percentage (DP), cut weight of hind legs (LW), weight ratio of cut hind legs to carcass (RLW), and weight of visceral and interscapular fat (WF), as well as two meat traits of the drip loss (DL) and cooking loss (CL) were phenotyped in a F1 crossbred population (N = 119) between Zika rabbits and Sichuan White rabbits. The effects of mRNA expression levels of a total of 10,288 genome-wide genes on these seven traits were statistically estimated using the mixed linear model, in which the polygenic background effects were accounted for. Our results revealed two candidate genes (RDH5 and MTARC2) that were statistically significantly associated with LW trait (the adjusted p values <0.05), whereas no gene reached the statistically significant threshold for all the remaining six traits. Because of the relatively small sample size analyzed, we alternatively selected 20 candidate genes with the lowest p values for every trait and subjected them to functional enrichment analyses, which identified three Gene Ontology (GO) terms that were significantly enriched by the candidate genes of CW and RLW traits. In conclusion, this study used TWAS approach to successfully reveal several candidate genes whose mRNA expression levels may be involved in regulating carcass and meat traits in meat rabbits, which are helpful to explore the underlying molecular mechanism in the future studies.